The Nationally Determined Contribution Expert Tool (NEXT): A Comprehensive Greenhouse Gas Accounting Tool to Support Annual Environmental Impact Assessment Over a 30-Year Time Series in the Agriculture, Forestry and Other Land Use Sector - Schiettecatte, Laure-Sophie; Audebert, Philip; Umulisa, Viviane; Dionisio, Daniel; Bernoux, Martial (Frontiers in Climate, 2022)
The Nationally Determined Contribution Expert Tool (NEXT) is a greenhouse gas accounting tool developed by the Food and Agriculture Organization of the United Nations (FAO) to support annual environmental impact assessment for the Agriculture, Forestry and Other Land Use sector (AFOLU). It provides a 30-year time series of annual and cumulated estimates of carbon removal and greenhouse gas emission reductions from actions determined by Parties in their climate policies. NEXT was developed using the Intergovernmental Panel on Climate Change (IPCC) methodologies, and estimates can be made using either the IPCC 2006 guidelines or the IPCC 2019 refinement to the IPCC 2006 which are both complemented with the IPCC 2013 Wetlands Supplement. The tool was designed to provide results that directly respond to the provisions of the Enhanced Transparency Framework and support the Nationally Determined Contributions (NDC) development as required by the modalities, procedures and guidelines. NEXT provides a detailed temporal series of results and a wide set of indicators, including the social value of carbon, enabling a comprehensive environmental and economic overview of climate actions in achieving mitigation targets. The tool helps countries to interpret, track and scale up ambition of their NDCs which could ultimately inform the global stocktake of the Paris Agreement in a harmonized way.